Iodination of aryl amines in a water-paste form via stable aryl diazonium tosylates; Tetrahedron Letters; Vol. 49, iss. 6 - Gorlushko D. A. Dmitry Aleksandrovich; Filimonov V. D. Viktor Dmitrievich; Krasnokutskaya E. A . Elena Aleksandrovna; Semenischeva N. I.; Bong Seong Go; Ho Yun Hwang; Eun Hye Cha; Ki-Whan Chi (2008, 2008)
Title screen